The natural courses of keratometric, pachymetric and visual acuity outcomes during 1year follow up after corneal collagen cross-linking - Rattan, . Suzan Amana (AL-Kindy College Medical Journal, 2016)
Background: As photochemical reaction that can stiffen the cornea, CXL is the only promising method of preventing progression of keratectasia such as KC and secondary ectasia following refractive surgery. The aim of CXL is to stabilize the underlying condition with a small chance of visual improvement. Objective: To show the sequences of changes in visual acuity and topographic outcomes during 1 year post CXL for patients with progressive Keratoconus.Type of the study: Cross sectional studyMethods: CXL procedure was done for 45 eyes with progressive KC. The following parameters had been monitored pre operatively, 1, 3, 6 and 12 months postoperatively: K apex, K2, corneal thickness at thinnest location, anterior and posterior elevation points, BCVA and UCVA. Placido –Scheimpflug topography (Sirius) device had been used to monitor the corneal parameters of the study. One –way ANOVA and Paired sample T test was used for statistical analysis.The study done in Lasik specialty center /Baghdad/IraqResults: At 1 year, an averages flattening of (2.11 D) diopter in K2 and (1.88 D) diopter in K apex were found. Mean BCVA improved by 1 line from (0.18) Log MAR to (0.13) Log MAR and mean UCVA improved by 3.5 lines from (0.89) to (0.64) log MAR. The corneal thickness at thinnest location was 5.71 Mm less than the baseline. All the above mentioned parameters showed a trend of worsening between the baseline and 1 month, and improvement thereafter. We found no statistically significant changes in the anterior elevation points while the posterior elevation point changed (increased) significantly.Conclusions: Corneal collagen cross-linking seems to be effective in decreasing progression of KC , with improvements in optical measures in many patients. Post operative parameters discussed within this review followed a seemingly reproducible trend in there natural course over 12 months .Generally, the trend that observed was immediate worsening between baseline and 1 month resolution at approximately 3 months, and improvement thereafter.